1993
DOI: 10.1152/jappl.1993.75.5.2273
|View full text |Cite
|
Sign up to set email alerts
|

Velocity profiles measured for airflow through a large-scale model of the human nasal cavity

Abstract: An anatomically accurate, x20 enlarged scale model of a healthy right human adult nasal cavity was constructed from computerized axial tomography scans for the study of nasal airflow patterns. Detailed velocity profiles for inspiratory and expiratory flow through the model and turbulence intensity were measured with a hot-film anemometer probe with 1 mm spatial resolution. Steady flow rates equivalent to 1,100, 560, and 180 ml/s through one side of the real human nose were studied. Airflows were determined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
202
0
6

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(225 citation statements)
references
References 0 publications
17
202
0
6
Order By: Relevance
“…Despite the small difference in area coverage, region D in the left cavity exhibits a small constricting section which causes a higher resistance in the flow and hence the smaller proportion of airflow through sections C, D and E. The flow in the left cavity stays close to the wall and its distribution is mainly in the middle sections and more dominant in the lower sections, while a small percentage (11.6%) is found in the upper section. This pattern was also observed in the work by Hahn, Scherer and Mozell (1993) and in the model of Keyhani, Scherer and Mozell (1995). In the right cavity the flow is concentrated within the middle sections.…”
Section: Flow Analysis and Heat Transfer In The Turbinate Regionsupporting
confidence: 78%
See 2 more Smart Citations
“…Despite the small difference in area coverage, region D in the left cavity exhibits a small constricting section which causes a higher resistance in the flow and hence the smaller proportion of airflow through sections C, D and E. The flow in the left cavity stays close to the wall and its distribution is mainly in the middle sections and more dominant in the lower sections, while a small percentage (11.6%) is found in the upper section. This pattern was also observed in the work by Hahn, Scherer and Mozell (1993) and in the model of Keyhani, Scherer and Mozell (1995). In the right cavity the flow is concentrated within the middle sections.…”
Section: Flow Analysis and Heat Transfer In The Turbinate Regionsupporting
confidence: 78%
“…It has, however, been shown experimentally that the oscillatory effects are not present until α = > 4 (Isabey and Chang, 1981). Additionally other studies have also concluded that under most conditions especially low flow rates, the nasal airflow can be considered quasi-steady (Chang, 1989;Hahn, Scherer and Mozell, 1993;Sullivan and Chang, 1991).…”
Section: Fluid Flow Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…For rats the frequency of sniffing is typically in the "theta" frequency range (4 -12 Hz) during olfactory discrimination (Rajan et al 2006;Uchida and Mainen 2003;Youngentob et al 1987) or exploration (Welker 1964), but how accurately sniffing frequency can be regulated and whether olfactory performance depends on the exact sniffing frequency is not known. Respiratory airflow and several other character-istics of sniffing covary with its frequency (Walker et al 1997;Youngentob et al 1987), so high frequencies could enhance olfactory transduction (Hahn et al 1993;Kimbell et al 1997). Alternatively, particular sniffing frequencies within the theta (4-to 12-Hz) range may be favorable for the coordination of olfactory processing with other brain regions (Kay 2005;Kepecs et al 2006;Komisaruk 1977).…”
Section: Introductionmentioning
confidence: 99%
“…They also reported the presence of a relatively large vortex and a smaller one in the upper and the floor of the region posterior to the nasal valve. Hahn et al (1993) created a 20 times magnified model and measured the flow velocity at several points in the five coronal 465 planes throughout the model with a hot film anemometer. They reported that the flow was laminar up to a breathing rate of 24 L/min.…”
Section: Introductionmentioning
confidence: 99%